PENERAPAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (ITE) TERHADAP CYBERBULLYING KEPADA PENGGEMAR K-POP - Dewi, Indah Purnama; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The main and most frequent impact of social media is cyber crime or crimes that occur around social media using internet networks. Cybercrime that often occurs is cyberbullying. The formulation of this problem includes what factors cause social media users to commit criminal acts of cyberbullying, and how effective the implementation of the ITE Law is on the role of criminal acts of cyberbullying on social media. The aim of this research is what factors cause a person or perpetrator to commit cyberbullying crimes, and to determine the effectiveness of the Information and Electronic Transactions Law in cases of cyberbullying on social media. The method used is the Normative Law method. The theory to assist this research uses differential association theory from Legal Criminology. This research obtained 5 (five) factors that cause a person/perpetrator to commit cyberbullying including, individual factors, school factors, peer factors/playmate factors, family factors, and factors using social media. Apart from that, the effectiveness of the ITE Law on social media has its pros and cons, there are those who respond that the ITE Law is effective, but there are also those who respond that it is not yet effective. However, if you look at the existing regulations, they are said to be effective because they have resolved problems using electronic media, but it comes back to law enforcement.Keywords: Effectiveness, Cyberbullying, Social Media